Pendampingan Teknik Gradasi Warna Untuk Meningkatkan Kreativitas Anak SD di Desa Mano’an - Kurniyah; Mohammad Zainuddin Yasid Zaidan (STIT Al - Ibrohimy Bangkalan, 2024)
The color gradation art mentoring program in Mano’an Village aims to enhance children's skills in drawing and coloring using the color gradation technique. According to Jean Piaget’s cognitive development theory, children aged 7 to 11, in the concrete operational stage, can comprehend visual concepts such as gradual color changes. This program is designed to help children in Elementary School (SD) master the color gradation technique using child-friendly media such as watercolor, colored pencils, and crayons. During the program, children are introduced to basic color concepts and trained to apply the gradation technique in their artwork. A coloring competition at the end of the program showed that 70% of participants demonstrated significant improvement in applying the color gradation technique. The program also successfully enhanced children's fine motor skills, creativity, and self-confidence. Collaboration with art teachers and parents ensured that the techniques learned could be continued after the program. The findings of this study show that teaching the color gradation technique not only improves the quality of children's artwork but also contributes to their cognitive and motor development.